Francis Bacon: The Logic of Sensation - Deleuze, Gilles 1925-1995 (London Bloomsbury, 2013)
Translated and with an Introduction by Daniel W. Smith Afterword by Tom Conley Gilles Deleuze had several paintings by Francis Bacon hanging in his Paris apartment, and the painters method and style as well as his motifs of seriality, difference, and repetition influenced Deleuzes work. This first English translation shows us one of the most original and important French philosophers of the twentieth century in intimate confrontation with one of that centurys most original and important painters. In considering Bacon, Deleuze offers implicit and explicit insights into the origins and development of his own philosophical and aesthetic ideas, ideas that represent a turning point in his intellectual trajectory. First published in French in 1981, Francis Bacon has come to be recognized as one of Deleuzes most significant texts in aesthetics. Anticipating his work on cinema, the baroque, and literary criticism, the book can be read not only as a study of Bacons paintings but also as a crucial text within Deleuzes broader philosophy of art. In it, Deleuze creates a series of philosophical concepts, each of which relates to a particular aspect of Bacons paintings but at the same time finds a place in the general logic of sensation. Illuminating Bacons paintings, the nonrational logic of sensation, and the act of painting itself, this workpresented in lucid and nuanced translationalso points beyond painting toward connections with other arts such as music, cinema, and literature. Francis Bacon is an indispensable entry point into the conceptual proliferation of Deleuzes philosophy as a whole. Gilles Deleuze (19251995) was professor of philosophy at the University of Paris, VincennesSt. Denis. He coauthored Anti-Oedipus and A Thousand Plateaus with Félix Guattari. These works, as well as Cinema 1, Cinema 2, The Fold, Proust and Signs, and others, are published in English by Minnesota.
Keywords: Bacon, Francis -- 1561-1626; 16th Century (1501-1600); 17th Century (1601-1700); Philosophy; United Kingdom